Kota Sebelum Mesin: Yogyakarta Periode 1950an-1970an - Eka Rahayu Manggasari (Universitas Gadjah Mada, 2019)
This study discusses the history of the Indonesian city from the perspective of the pedicab peddlers from the 1950s to the 1970s. The role of the pedicab peddlers was central in transporting people and goods in the cities. The stagnation of public transportation, which had started since the Japanese occupation, had worsened in the postcolonial period. The failure to find a substitute for public transport resulted in its replacement with human labor, in the form of the pedicab. The article argues that the centrality of the pedicab during the early decades of independence means that to understand how urban spaces were experienced required an understanding of their function for these urban spaces. Their role need to be given voice to the narrative of the city. Pedicabs worked in tehe urban streets and are integral to the functioning of the street. The article wants to explore the writing of the history of the city, in which human power plays a central role. In depth the purpose of this kind of writing will open our eyes to our understanding of how the city works at the street level.